Land use changes effect by slash and burn cultivation to understory diversity composition and soil degradation - Setiawan, Adi; Pamungkas, Bayu Aji; Ito, Satoshi; Ramadhan, Varotama Putra; Lestariningsih, Iva Dewi; Khumairoh, Uma; Arifin, Syamsul; Wicaksono, Karuniawan Puji; Udayana, Cicik; Kurniawan, Yani; Tyasmoro, Setyono Yudo; Saitama, Akbar; Permanasari, Paramyta Nila; Syib'li, Muhammad Akhid; Aini, Luqman Qurata (Journal of Degraded and Mining Lands Management, 2024)
This study contributes to understanding ecological changes in land use following slash-and-burn land clearing. This study aimed to compare the richness and density of plant species and soil fertility in farmland cultivated for one year (1 Y), three years (3 Y), and five years (5 Y) after slash-and-burn, with the conditions in the secondary forest (SF) in Berau Regency of East Kalimantan. Understory plant taxon types, numbers, and soil organic matter were measured in each region using a series of nested plots. The size of each observation plot was 20 x 100 m. Data on understory vegetation composition was collected using 1 x 1 m mini plots at 20 sampling points and divided into five blocks, with a 10 m spacing between sampling points on each property. Understory vegetation species and cover percentage, litter cover percentage, open soil percentage, and soil fertility were measured for each observation plot. The results showed that the land cover percentage increased each year during the 5 years transition from secondary forest to farmland. Furthermore, within the 5 years, there was a change in understory species, particularly the presence of grasses and sedges at 3 and 5 years after the land use change. However, the transition from secondary forest to farmland within 5 years did not alter soil organic matter and total nitrogen.